(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This text was produced following an invitation to the author to participate in the International Colloquium Après La Scène: Les Autres Vies de la Marionnette, organized by the Centre National du Costume et de la Scène, in Moulins (France). The theme of the colloquium sought to mobilize reflections on the problem that involves the survival of the figures created for Puppet Theater, when the repertoires are no longer active or when the groups that gave rise to them end. In this work, orbiting about the term "rest", understood as that which resists disappearance, as the place of inscription and testimony of time, the author focuses on the objects and the place they occupy in our societies. The relationship with time is also analyzed, based on the questioning of what a society prohibits itself from destroying or sacrificing, based on what remains, what stays. What could be our relationships, in time, with these works, located in another context? What dynamics are possible beyond the scene?